Metode ohmic heating untuk ekstraksi betasianin sebagai pewarna pangan dari kulit buah naga merah (Hylocereus polyrhizus): Ohmic heating method for betacyanin extraction from red dragon fruit peels (Hylocereus polyrhizus) - Nurbaya, Syarifa Ramadhani; Saidi, Ida Agustini; Syahrorini, Syamsudduha; Machfudz, Al; Kusumawati, Elena Febri (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
Natural food colorant is increasingly being developed and applied to food products. Natural food coloring is safer to use because it does not cause side effects to health. Indonesia is rich in the availability of red dragon fruit. In general, people only eat dragon fruit flesh, while the skin is not used. Red dragon fruit skin is rich in betacyanin pigment which produces a red-violet color. This pigment needs to be extracted so that it is separated from other skin components. Extraction using ohmic heating technology can be a solution to extract betacyanin pigment. The aim of the study was to determine the characteristics of the betacyanin pigment from red dragon fruit skin extracted using the ohmic heating method. The study used a factorial randomized block design consisting of two factors, the first factor was the type of solvent (aquades, 0.25% NaCl solution, 0.25% citric acid) and the second factor was the amount of voltage (30 V, 40 V, 50 V). The results showed that the highest betacyanin content was found in the 0.25% NaCl solvent treatment, which was 5.15 mg/L. Extracts stored in the refrigerator for 5 days did not show a significant change in extract betacyanin pigment levels.